Athletes with valvular heart disease and competitive sports: a position statement of the Sport Cardiology Section of the European Association of Preventive Cardiology. (13th April 2021) - van Buuren, Frank; Gati, Sabiha; Sharma, Sanjay; Papadakis, Michael; Adami, Paolo Emilio; Niebauer, Josef; Pelliccia, Antonio; Rudolph, Volker; Börjesson, Mats; Carre, Francois; Solberg, Erik; Heidbuchel, Hein; et al.
Abstract: This article provides an overview of the recommendations from the Sports Cardiology section of the European Association of Preventive Cardiology on sports participation in individuals with valvular heart disease (VHD). The aim of these recommendations is to encourage regular physical activity including sports participation, with reasonable precaution to ensure a high level of safety for all affected individuals. Valvular heart disease is usually an age-related degenerative process, predominantly affecting individuals in their fifth decade and onwards. However, there is an increasing group of younger individuals with valvular defects. The diagnosis of cardiac disorders during routine cardiac examination often raises questions about on-going participation in competitive sport with a high dynamic or static component and the level of permissible physical effort during recreational exercise. Although the natural history of several valvular diseases has been reported in the general population, little is known about the potential influence of chronic intensive physical activity on valve function, left ventricular remodelling pulmonary artery pressure, and risk of arrhythmia. Due to the sparsity of data on the effects of exercise on VHD, the present document is largely based on clinical experience and expert opinion.